Med queer teorijami, queer politikami in gejevsko-lezbičnimi gibanji - Perger, Nina (Družboslovne razprave, 2014)
The purpose of this paper is to analyse queer politics and their theoretical framework along with queer theories, and to compare them to the identity politics of gay and lesbian movements. Queer politics and queer theories are critical of the exclusionary logic of identity politics since the latter only include those subjects who meet the criteria for specific - gay and lesbian - identity categories, which serve as a basis for political representation in which non-normative subjects are excluded. Queer subjects are opposed to these exclusive identity categories and concepts of (hetero- and homo-) normativity by positioning themselves outside of identity binarisms in the field of gender and sexuality - in the case of queer disidentity queer politics and struggles are established on the basis of common interests, not identities. Queer politics and queer theories thus offer legitimate criticism of gay and lesbian movements.
Keywords: Gay studies; Gejevske študije; Lesbian studies; Lezbične študije; študije spolov; spolna identiteta